Correlations of High-frequency Ultrasound Evaluation of Brachial Artery Endothelial Dilatation and Carotid Atherosclerosis with Glucose and Lipid Metabolism, Inflammatory Cytokines, Severity of Coronary Artery Disease and Vascular Endothelial Function in Elderly Patients: Ultrasound Evaluation on Coronary Artery Disease - Cheng, Yutong; Sun, Tao; Yin, Chengqian; Wang, Su; Li, Zhao; Tao, Ying; Li, Zhizhong; Zhang, Hongju (Cellular and Molecular Biology, 2022)
The study aimed to explore the correlations of the results of the high-frequency ultrasound evaluation of the brachial artery endothelial dilatation and carotid atherosclerosis with glucose and lipid metabolism, inflammatory cytokines, the severity of coronary artery disease (CAD) and vascular endothelial function in elderly patients. 78 elderly patients with CAD in Beijing Anzhen Hospital were selected. The high-frequency ultrasonography was carried out to observe the flow-mediated dilatation (FMD) and intima-media thickness (IMT) and to analyze their correlations with inflammatory cytokines [C-reactive protein (CRP) and plasminogen activator inhibitor (PAI-1)], endothelial function [nitric oxide (NO) and endothelin-1 (ET-1)], glycolipid metabolism [high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), triglyceride (TG) and fasting blood glucose (FBG)] and the severity of CAD. FMD, NO and HDL-C: patients with single-vesselCAD> those with double-vessel CAD>those with multi-vessel CAD. IMT, CRP, PAI-1, FBG, ET-1, TC and TG: patients with single-vesselCAD< those with double-vessel CAD <those with multi-vessel CAD (p<0.05). The FMD had negative correlations with CRP, PAI-1, FBG, ET-1, TC and TG and positive correlations with NO and HDL-C (p<0.05). The IMT was positively associated with CRP, PAI-1, FBG, ET-1, TC and TG and negatively related to NO and HDL-C (p<0.05). As the disease becomes severe, the endothelial dilatation of brachial arteries in elderly patients with CAD becomes weaker, and the risk of carotid atherosclerosis increases.